CircRNA hsa_circ_0013958 may contribute to the development of ovarian cancer by affecting epithelial‐mesenchymal transition and apoptotic signaling pathways. Issue 7 (10th March 2020) - Pei, Cheng; Wang, Han; Shi, Cong; Zhang, Chuanqi; Wang, Min
Abstract: Background: CircRNA plays an important role in the development of tumors, but its mechanism of action in ovarian cancer is still unclear. Methods: The expression level of hsa_circ_0013958 in 45 pairs of ovarian cancer tissues and cells was quantified by qRT‐PCR, further revealing whether it is related to clinicopathological features and diagnostic value. Next, the effects of hsa_circ_0013958 on the proliferation, migration, invasion, and apoptosis of A2780 and OVCAR‐3 cells were detected by CCK‐8 assay, Transwell assay, and flow cytometry, respectively. Last, the expression levels of epithelial‐mesenchymal transition‐related proteins (E‐cadherin and Vimentin) and apoptosis‐related proteins (Bcl‐2 and Bax) were detected by Western blotting. Results: Hsa_circ_0013958 was highly expressed in ovarian cancer tissues and cells, and its expression was closely related to patient FIGO stage and lymph node metastasis. Further, in vitro studies showed that knockdown of hsa_circ_0013958 suppressed proliferation, migration, and invasion of ovarian cancer cells but elevated the cell apoptotic rate. The expression levels of both epithelial‐mesenchymal transition‐related proteins and apoptosis‐related proteins were also changed. Conclusions: Hsa_circ_0013958 may contribute to the development of ovarian cancer by affecting epithelial‐mesenchymal transition and apoptotic signaling pathways.